1993
DOI: 10.1002/ajh.2830420408
|View full text |Cite
|
Sign up to set email alerts
|

Loss of high‐responder inhibitors in patients with severe hemophilia A and human immunodeficiency virus type 1 infection: A report from the multi‐center hemophilia cohort study

Abstract: To evaluate the effects of human immunodeficiency virus type 1 (HIV-1) infection on the loss of factor VIII alloantibodies, we identified 77 patients with a history of inhibitors from among a large cohort of HIV-1-infected participants enrolled in a natural history study of HIV-1 infection in hemophilia. Fifty-six patients were high responders with inhibitors titers greater than 5 Bethesda Units (BU) measured on at least one occasion. From May 1985 to December 1989, 13 of the high-responder patients were recha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 19 publications
0
89
0
1
Order By: Relevance
“…A similar result was also seen when the experiment was independently repeated with the more complete B-cell depletion using IgG2a anti-CD20 ( Figure 2D). It is known that inhibitor formation is T cell-dependent in both humans and mice, 6,[18][19][20] and it has been reported that B cells are required for optimal CD4 T-cell function. 21 Thus, the elimination of the majority of B cells may be responsible for the lack of boosting.…”
Section: Resultsmentioning
confidence: 99%
“…A similar result was also seen when the experiment was independently repeated with the more complete B-cell depletion using IgG2a anti-CD20 ( Figure 2D). It is known that inhibitor formation is T cell-dependent in both humans and mice, 6,[18][19][20] and it has been reported that B cells are required for optimal CD4 T-cell function. 21 Thus, the elimination of the majority of B cells may be responsible for the lack of boosting.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] FVIII-specific antibodies are dependent on CD4 ϩ T helper (T H ) cells, 4 which respond to FVIIIderived peptides bound to major histocompatibility complex class II receptors on antigen-presenting cells when these class II-peptide complexes bind with sufficient avidity to their T-cell receptors, causing proliferation and cytokine release. CD4 ϩ T cells may be divided into 4 subsets that secrete distinct cytokines, as follows: T H 1, T H 2, inducible regulatory T cells, and the recently defined T H 17 cell lineage.…”
Section: Introductionmentioning
confidence: 99%
“…12 FVIII-specific T cells have been identified in the peripheral blood of hemophilia A patients with inhibitor using T-cell proliferation assays with native FVIII. 13 The epitopes recognized by such T cells were studied using synthetic peptides covering the entire FVIII molecule.…”
Section: Introductionmentioning
confidence: 99%